Isolation and characterisation of Alternaria brassicae (Berk.) Sacc from Brassica spp. from diverse agro-climatic zones of India - Singh, H K; Manish, K M; Divya, S; Shubham, P; Ajay, K; Vikas, Y; Mishra, D S; Prakash, Y; Anad, S; Aina, Y; et al. (Plant Science Today, 2026)
Alternaria brassicae (Berk.) Sacc, a necrotrophic pathogen, is responsible for up to 48 % yield loss in rapeseed-mustard. Therefore, a study was carried out at the laboratories of the Department of Plant Pathology, Acharya Narendra Deva University of Agriculture and Technology, Narendra Nagar (Kumarganj), Ayodhya (UP), during Rabi season 2019–20 and 2020–21. In this study, ten isolates of A. brassicae were collected from infected leaf samples across different Indian states and evaluated for cultural and morphological variability. Significant differences were observed among isolates with respect to conidiophore and conidial traits, septation and growth on various media. Conidiophore length ranged from 33.28 µm (Abr2) to 66.44 µm (Abr7), while width varied from 4.83 µm (Abr1) to 7.72 µm (Abr3). Septation in conidiophores was highest in Abr3 (6.66) and lowest in Abr4 (4.00). Conidial dimensions also showed variability, with maximum length (146.45 µm), width (18.36 µm) and beak length (73.46 µm) recorded in Abr3, whereas Abr2 exhibited the lowest measurements. Horizontal septa ranged from 5.66 (Abr2) to 8.66 (Abr6, Abr7) and longitudinal septa ranged from 0.33 (Abr2) to 2.66 (Abr3). Mycelial growth assessment on five solid media, viz. PDA, oatmeal agar, host leaf extract agar, czapek dox agar and carrot juice agar, revealed isolate-specific responses. Abr3 consistently showed the highest radial growth on PDA (90.00 mm), czapek dox (55.64 mm) and carrot juice agar (76.78 mm), while Abr2 and Abr10 exhibited minimal growth. Colony colour varied from light brown to black across media, with appearance ranging from compressed to fluffy and margins from smooth to wavy. This variability among A. brassicae isolates is critical for understanding pathogen diversity and for resistance breeding strategies in Brassica crops.